Pathological Characteristics, Prognostic Determinants and the Outcome of Patients Diagnosed with Colorectal Adenocarcinoma at the University Teaching Hospital of Kigali - Uwamariya, Delphine; Ruhangaza, Déogratias; Rugwizangoga, Belson (Canadian Journal of Gastroenterology and Hepatology, 2022)
Worldwide, colorectal cancer (CRC) is the second most diagnosed cancer in female and the third in men, arising from the epithelium of the colorectum. It is known that colorectal cancer is common in developed countries than in developing countries which may be due to inaccurate data on the existence of the disease in that region combined with embracing western lifestyle expressed by the current trend of changes in cultural, social, and lifestyle practices playing a major part in the etiology of CRC. The aim of this study was to document epidemiological, pathological characteristics, and prognostics determinants of patients diagnosed with CRC in Rwanda. The data from patients’ files and reviewed glass slides for 101 cases all from Kigali University Teaching Hospital (CHUK) were statistically analyzed and patient characteristics were described as mean and frequency accordingly. Comparisons were performed using chi square tests, Fisher’s exact test and odds ratio with 95% confidence interval (CI). Survival curves were plotted using the Kaplan–Meier method, and log-rank test was used to assess the statistical differences in the observed survival curves by each categorical variable. A P value < 0.05 was considered statistically significant. Statistical analyses were performed using Statistical Product and Service Solutions (SPSS), GraphPad Prism, and MedCalc, accordingly. Mean age of the participants was 54.26 years, the main symptom was rectal bleeding (46.5%), rectal adenocarcinoma NOS represented 40.6%, conventional adenocarcinoma was 60.4%, most tumors were of Grade II (54.5%), most common stage was pT3N0 (20.8%), resection margins were free at 71.3%, lympho-vascular invasion was 49.5% of cases, a high immune response was in 71.3% of cases and of 101cases, and 55.4% were still alive at the end of the data collection, with 29.3% of patients have overall survival of 5 years. Prognostic determinants also affect the outcome in this study and overall survival period was 3 years for CRC diagnosed in Rwanda.